ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEAKTIFAN BELAJAR SISWA SEKOLAH DASAR - Suci Rahmadani; Mufarizuddin Mufarizuddin; Yanti Yandri Kusuma (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2023)
The background of this research is to describe the factors that influence the learning activity of elementary school students. This research is a qualitative descriptive study. The subjects of this study were fifth grade students of SD Negeri 004 Bangkinang Kota. Methods of data collection using observation and interviews. The data analysis technique uses data reduction, data presentation, and drawing conclusions. The data validity technique uses source and technique triangulation. The results showed that the internal factors that affect the learning activity of fifth grade students are (1) physiological factors, namely physical (sensory) and physical conditions, (2) psychological factors, namely attention, memory, and responses. External factors that affect the learning activity of fifth graders are (1) social factors, namely teachers and peers, (2) non-social factors, namely places and facilities. The dominant factor that affects the learning activity of class V students is the student's psychological factor.